ANALISIS PENGARUH CURAH HUJAN TERHADAP EROSI PADA TANAH TANPA MULSA DAN DIBERI MULSA - Tesa Gloria Tumangkeng; Verry R.Ch, Warouw; Jody M. Mawara (COCOS, 2021)
AbstractThe purpose of this study is to know how rainfall affects soil erosion without mulch and soil erosion with mulch treatment.It is one of the resources that play an important role in the survival of organisms. Rainfall is one of the great climatic elements thatplay a role in avalanches and erosion (sutedjo and kartasapoetra, 2002). Rainwater that falls on the earth will result in erosion ofthe soil in its path. One of the techniques for land and water conservation is that of mulsa (pratiwi, 2007). The method used in thisstudy is a secondary data analysis method. The number of data studied by as many as 34 samples through simple, linear regressionanalysis methods. Studies suggest that there is a tendency that the higher the precipitation, the more soil erosion is produced. Asfor the linrelation equation, it is Y1 = - 1304.4+ 81.411X with r efficiency = 0986 and Y2 = 58,891X - 933.26 with an r.0,985.Research obtained a value of significance by as high as,000 < 0.05; It could be concluded that the hypothesis (h1) that reads "rainfallhas a positive effect on erosion with and without any kind of mulch," is accepted. Regression coefficient effect of rainfall on erosionwith mulsa treatment is y2 = 81.411-22.5. Can be seen that the regression coefficient of dx is <001. This shows very clearly thecontrast in mulched soil erosion, its erosive drop by as much as 2.2.5 grams.Keywords: Rainfall, Mulch, Erosion.